In situ nano-objects via RAFT aqueous dispersion polymerization of 2-methoxyethyl acrylate using poly(ethylene oxide) macromolecular chain transfer agent as steric stabilizer. (12th October 2015) - Sugihara, Shinji; Ma'Radzi, Akmal Hadi; Ida, Shota; Irie, Satoshi; Kikukawa, Takamaru; Maeda, Yasushi
Abstract: Poly(ethylene oxide)-poly(2-methoxyethyl acrylate) diblock copolymers (PEO- b -PMEA) are synthesized by RAFT aqueous dispersion polymerization of MEA using poly(ethylene oxide) macromolecular chain transfer agent as a reactive steric stabilizer. Both segments are well-known to be bio- and blood-compatible polymers. This formulation enables the production of various particle morphologies such as spheres, worms, and vesicles from the same block copolymer in water. The synthesis starts when both the reactive steric stabilizer and MEA monomer are dissolved in water; however, the growing polymer is not water-soluble and begins to form nano-objects. In the case of the synthesis of PEO113 - b -MEA300 diblock copolymers, the nano-objects change from spheres into larger aggregates of worms when the solids concentration in the polymerization increases from 5 to 15 wt% at full monomer conversion. The morphology finally turns into vesicles as the solids concentration increases to 20 wt%. The final block copolymer morphology at full monomer conversion is dictated by not only degree of polymerization of MEA but also the solids concentration in the polymerization mixture. Graphical abstract: Highlights: This work proposes polymerization induced self-assembly for PEO- b -PMEA. RAFT aqueous dispersion polymerization of MEA using PEO macro-CTA was conducted. Various morphologies such as sphere, worm, and vesicle can be produced. The final morphology can be dictated not only DP of MEA but also the solids concentration in the polymerization mixture.